Manajemen Pendidikan di Tengah Pertentangan Nilai, Kebijakan, dan Kepentingan Stakeholder - Zuwaibatul Aslamiyah; Romi Rizal Fauzi; Salman Al Farisi; Muhammad Saifurrahman (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to analyze the forms of conflicts that arise within the educational environment and their implications for educational management. The research employs a quantitative approach based on library research by reviewing relevant journal articles published between 2020 and 2025 that address value conflicts, educational policies, and inter-stakeholder interests. The results indicate that value conflicts are often influenced by cultural differences, parenting styles, technological developments, and friction between traditional and modern values in schools. Policy conflicts emerge when national policies are not aligned with the readiness of facilities, teachers’ competencies, and school contexts. Meanwhile, conflicts of interest occur due to differing priorities among teachers, school principals, parents, and the government. These findings emphasize the importance of implementing adaptive and collaborative management strategies. This article provides an overview of an ideal educational management model to address conflicts and identify opportunities for improvement in the future.